Improving Teaching and Research Capacity in Indonesia Education Throught ASEAN Collaboration - Didik Sulistyanto (International Conference on Education and Language (ICEL), 2014)
In the global higher education (HE) scenario, many countries face common challenges in higher education  including rising demands for access to higher education, and the needs to improve the quality of higher education  for international recognition. Although the harmonisation of HE process in Europe has not been without flaws, a regional platform to address and perhaps solve common challenges in higher education  is of interests to the global regions. This project examines the teaching and research capacity of hight education in the case of ASEAN countries. Education for All (EFA) is a drive to decentralize basic and secondary educational planning, management and accountability, particulary in countries with highly centralized systems of governance, to make themm more responsive to diverse local needs and place more responsibility at the local level. The decentralization of higher education also played a part in Indonesia’s many post-revolutionary reforms, and the Indonesian goverment identified a group of top tier universities to become more independent from central control. Considering a regional commitment to establish an ASEAN Community by 2015 and the international challenges in higher education, a more prominent role of the harmonisation of higher education  process within the ASEAN region is crucial to build a strong foundation for the ASEAN Community and also to enhance higher education interconnectedness of ASEAN and beyond. This study explores the teaching and research capacity of Indonesia education , particularly from an ASEAN perspective. It also investigates the progress and impediments towards increased human resources development in Indonesia education in this region of ASEAN, to promote the connectivity in education among ASEAN countries and beyond.